Alternative Routes for the Formation of Immunochemically Distinct Advanced Glycation End-products In Vivo - Takeuchi, M.; Makita, Z. (Current Molecular Medicine, 2001)
The advanced stage of the glycation process (also called the “Maillard reaction”) that leads to the formation of advanced glycation end-products (AGEs) plays an important role in the pathogenesis of angiopathy in diabetic patients and in the aging process. AGEs elicit a wide range of cell-mediated responses that might contribute to diabetic complications, vascular disease, renal disease, and Alzheimer disease. Recently, it has been proposed that AGE are not only created from glucose per se, but also from dicarbonyl compounds derived from glycation, sugar autoxidation, and sugar metabolism. However, this advanced stage of glycation is still only partially characterized and the structures of the different AGEs that are generated in vivo have not been completely determined. Because of their heterogeneity and the complexity of the chemical reactions involved, only some AGEs have been characterized in vivo, including N-carboxymethyllysine (CML), pentosidine, pyrraline, and crosslines. In this article, we provide a brief overview of the pathways of AGE formation and of the immunochemical methods for detection of AGEs, and we also provide direct immunological evidence for the existence of five distinct AGE classes (designated as AGE-1 to -5) within the AGE-modified proteins and peptides in the serum of diabetic patients on hemodialysis. We also propose pathways for the in vivo formation of various AGEs by glycation, sugar autoxidation, and sugar metabolism.
Keywords: glycation end-products (AGEs)